2014
DOI: 10.1890/14-0211.1
|View full text |Cite
|
Sign up to set email alerts
|

Heterospecific pollen receipt affects self pollen more than outcross pollen: implications for mixed‐mating plants

Abstract: Flowering plants often occur in mixed-species groups where interactions between them can occur both pre-and post-pollination. In post-pollination interactions, conspecific (CP) and heterospecific pollen (HP) interact on the style and previous work indicates that these interactions, often, but not always, lead to reduced fitness. However, over half of insect-pollinated species display a mixed mating system, where both self and outcross CP could interact with HP, yet no study has evaluated the effects on both ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 53 publications
(110 reference statements)
2
15
0
Order By: Relevance
“…Our findings that receipt of S. polygaloides pollen reduced M. guttatus tube growth and seed production corroborate those from studies with other heterospecific pollen donors of M. guttatus (e.g., Heracleum mantegazzianum Sommier & Levier, Helianthus exilis A.Gray, Stachys albens A.Gray, Mimulus nudatus Curran ex Greene) (Nielsen, et al, 2008; Arceo‐Gómez and Ashman, 2011, 2014a). A 25% reduction in the proportion of pollen tubes reaching the ovary in response to S. polygaloides pollen receipt is similar to the ∼22% reduction in pollen tube growth Arceo‐Gómez and Ashman (2014a) reported when H. exilis pollen acted as a heterospecific pollen donor to M. guttatus .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings that receipt of S. polygaloides pollen reduced M. guttatus tube growth and seed production corroborate those from studies with other heterospecific pollen donors of M. guttatus (e.g., Heracleum mantegazzianum Sommier & Levier, Helianthus exilis A.Gray, Stachys albens A.Gray, Mimulus nudatus Curran ex Greene) (Nielsen, et al, 2008; Arceo‐Gómez and Ashman, 2011, 2014a). A 25% reduction in the proportion of pollen tubes reaching the ovary in response to S. polygaloides pollen receipt is similar to the ∼22% reduction in pollen tube growth Arceo‐Gómez and Ashman (2014a) reported when H. exilis pollen acted as a heterospecific pollen donor to M. guttatus .…”
Section: Discussionsupporting
confidence: 89%
“…Thus, plants commonly receive pollen loads that contain both heterospecific and conspecific pollen (Ashman and Arceo‐Gómez, 2013; Arceo‐Gómez et al, 2015 in this issue). The receipt of mixed‐species pollen loads may have negative effects on recipient reproduction, as heterospecific pollen can interfere with adhesion, hydration, germination, and tube growth of conspecific pollen, as well as reduce ovule and seed development (Sukhada and Jayachandra, 1980; Thomson et al, 1982; Galen and Gregory, 1989; Arceo‐Gómez and Ashman, 2011, 2014a). For instance, a recent synthesis found that all species received heterospecific pollen in at least some of their flowers (range 2–100% of flowers), and hand pollinations with a standard mixed load of heterospecifc and conspecific pollen led to a significant (mean 20%) decrease in seed production (Ashman and Arceo‐Gómez, 2013).…”
mentioning
confidence: 99%
“…; Waser & Price ; de Jong et al . ) or (3) its germination is affected by HP deposition (Arceo‐Gómez & Ashman ). Perhaps more pollination quality effects might have been detected if, for instance, pollen‐tube survival rather than germination rates had been measured because pollen‐tube growth is a better indicator of genetically and environmentally driven pollen–pistil interactions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to recognize and reject heterospecific pollen, therefore, is important to prevent wasted ovules as well as to maintain species integrity. Outcrossing species in complex plant communities often are challenged by heterospecific pollen (Arceo-Gómez and Ashman, 2014) and, thus, would be expected to maintain robust interspecific pollen recognition and rejection mechanisms.…”
mentioning
confidence: 99%